Cortisol awakening response in the airborne rescue service. (5th June 2022) - Braun, D; Frank, M; Theiler, L; Petrowski, K
Abstract: Background: Work-related stress may lead to mental and physical illnesses. Emergency physicians may be particularly vulnerable to developing such diseases due to their extreme emotional working environment. Aims: The purpose of the study was to analyse the hormonal stress burden of emergency physicians in the airborne rescue service to create an empirical basis for developing appropriate measures against chronic stress in the rescue service. Methods: Three salivary cortisol samples were collected after awakening in 15 min intervals—each on a flight rescue day, a clinic day and a free day—to calculate the extent of the hormonal stress load of the emergency physicians. A nested linear mixed-model analysis was used in 40 cases to investigate hormonal stress. Furthermore, professional years and gender were included in the calculations. Results: The mixed model showed neither a main effect for measurement time nor for day but a significant interaction effect ( P = 0.002). The cortisol level rises strongly on the flight rescue and the clinic day, while on the free day it shows a moderate increase. Professional years and gender also proved to be statistically significant for the cortisol level of emergency physicians ( P < 0.001). Conclusions: The results show a significantly higher cortisol increase on working days compared with a free day, which indicates a stronger stress burden on working days of emergency physicians in the airborne rescue service. Future studies should examine the stress level of emergency physicians in more detail to prove whether the working conditions of emergency physicians need to be modified.